La Potencialidad Oculta de los Recubrimientos - González, J.C. (2020)
Nowadays the growth of technological materials in the form of thin lms, layers, or coatings, still remains like one of the topics of greatest vitality, in both the scientic and technological environment. These technological materials already are in various applications of the dierent products that we use on our daily basis. However, how technology on coatings can help the country's productive sector?. We briey describe this hidden potential of coatings through this communication to help close the gap between the knowledge production in the academy and the work tools that the Peruvian industry sector needs to improve the quality of its nal products.